Model of Illusions and Virtual Reality - Gonzalez-Franco, Mar; Lanier, Jaron (Frontiers in Psychology, 2017)
In Virtual Reality (VR) it is possible to induce illusions in which users report and behave as if they have entered into altered situations and identities. The effect can be robust enough for participants to respond “realistically”, meaning behaviors are altered as if subjects had been exposed to the scenarios in reality. The circumstances in which such VR illusions take place were first introduced in the 80’s. Since then, rigorous empirical evidence has explored a wide set of illusory experiences in VR. Here we compile this research and propose a neuroscientific model explaining the underlying perceptual and cognitive mechanisms that enable illusions in VR. Furthermore, we describe the minimum instrumentation requirements to support illusory experiences in VR, and discuss the importance and shortcomings of the generic model.